Peningkatan Kompetensi Pelaku UMKM melalui Program Pelatihan dan Pendampingan di Desa Margaluyu, Tanjungsari Sumedang - Adhitya Ikhsani Wardhana; Endang Silaningsih; Tini Kartini (Universitas Muhammadiyah Palembang, 2025)
Purpose – This study examines the impact of training and mentoring individually and jointly, on improving the competence of MSME actors. Design/methodology – A quantitative approach was employed, using survey questionnaires targeting 43 MSME practitioners in Margaluyu Village who are engaged in product manufacturing. Data were analyzed using instrument validity testing, classical assumption checks, and regression analysis to examine the proposed hypotheses. Findings - The results indicate that both training and mentoring significantly influence the competence of MSME actors, whether implemented partially or simultaneously have a strong positive influence on the competence of MSME actors. When combined, the effect is even more pronounced. This suggests that the government should develop and implement MSME development programs that integrate structured training with ongoing mentoring. Additionally, MSME actors are encouraged to actively participate in training sessions and fully utilize mentoring opportunities to continually improve their business skills and competencies.